2019
DOI: 10.1111/ivb.12254
|View full text |Cite
|
Sign up to set email alerts
|

Distributional dynamics of a specialized subterranean community oppose the classical understanding of the preferred subterranean habitats

Abstract: Troglobionts are organisms that are specialized for living in a subterranean environment. These organisms reside prevalently in the deepest zones of caves and in shallow subterranean habitats, and complete their entire life cycles therein. Because troglobionts in most caves depend on organic matter resources from the surface, we hypothesized that they would also select the sections of caves nearest the surface, as long as environmental conditions were favorable. Over 1 year, we analyzed, in monthly intervals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 79 publications
2
11
0
Order By: Relevance
“…A three‐year study revealed an exceptionally high species richness of soil Collembola in Silická ľadnica Ice Cave, specifically 129 species within a very small area of 351 m 2 , and the presence of diverse microrefugia for many endemic and climatic relict taxa, such as cold‐adapted (psychrophilic) species with montane, disjunctive boreo‐montane and arctic–alpine distribution ranges (Raschmanová, Miklisová, et al, 2018). Generally, cave entrances represent dynamic environments with characteristic microclimate fluctuations (e.g., Mammola et al, 2017; Moldovan et al, 2018; Raschmanová, Šustr, et al, 2018) and are also considered to be functional ecotones for epigean (surface) and subterranean systems, revealing high local diversity and endemism of arthropods (Culver, 2005; Culver & Poulson, 1970; Kozel et al, 2019; Mammola et al, 2017; Papáč et al, 2019; Prous et al, 2004, 2015; Raschmanová, Miklisová, et al, 2018; Yao et al, 2016). Furthermore, the specific conditions of permanently cold habitats (near the floor ice) at the cave entrance may enhance speciation and diversity of arthropod communities, including cryptic taxa (Raschmanová et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A three‐year study revealed an exceptionally high species richness of soil Collembola in Silická ľadnica Ice Cave, specifically 129 species within a very small area of 351 m 2 , and the presence of diverse microrefugia for many endemic and climatic relict taxa, such as cold‐adapted (psychrophilic) species with montane, disjunctive boreo‐montane and arctic–alpine distribution ranges (Raschmanová, Miklisová, et al, 2018). Generally, cave entrances represent dynamic environments with characteristic microclimate fluctuations (e.g., Mammola et al, 2017; Moldovan et al, 2018; Raschmanová, Šustr, et al, 2018) and are also considered to be functional ecotones for epigean (surface) and subterranean systems, revealing high local diversity and endemism of arthropods (Culver, 2005; Culver & Poulson, 1970; Kozel et al, 2019; Mammola et al, 2017; Papáč et al, 2019; Prous et al, 2004, 2015; Raschmanová, Miklisová, et al, 2018; Yao et al, 2016). Furthermore, the specific conditions of permanently cold habitats (near the floor ice) at the cave entrance may enhance speciation and diversity of arthropod communities, including cryptic taxa (Raschmanová et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a few cases, troglobionts also occurred in close proximity to the surface, although in low numbers. This was not an unexpected pattern as it has been shown that obligate subterranean species within different cave systems may present a bimodal distribution, with peaks in richness and abundance in close proximity to the surface and deeper inside caves (Novak et al, 2012;Kozel et al, 2019). Yet, in the cave system of Comba dell'Infernotto, the predicted and observed abundance in the vicinity of the surface was close to zero (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Troglobitic organisms might have suffered different ecological pressures over time when compared to troglophiles and trogloxenes, hence occupying an entirely different niche. Being adapted to the dark and oligotrophic cave environment, they can inhabit places that are not tolerable for most cave dwellers (Kozel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have tried to elucidate the main environmental factors driving the invertebrate community structure (species richness and composition) in cave environments. The main factors highlighted as important are seasonality (Tobin et al, 2013;Mammola et al, 2015;Bento et al, 2016;Lunghi et al, 2017;Kozel et al, 2019), lithology (Souza-Silva et al, 2011b), landscape structure (Christman et al, 2016;Mammola & Leroy, 2017), distance from cave entrance (Ferreira & Martins, 1998;Prous et al, 2004;Tobin et al, 2013;Kozel et al, 2019), linear development of the cave (Simões et al, 2015;, presence…”
Section: Introductionmentioning
confidence: 99%